Fake Science/Nutrition News: Part 2—Trust. Issue 4 (July 2018) - Rowe, Sylvia; Alexander, Nick
Abstract : As has been widely explored in the literature, the evolving science-communication landscape has posed challenges to the credibility and trustworthiness of nutrition and health communicators. Especially, the Internet-mediated democratization of expertise, where every blogger and Web site owner becomes a subject-matter expert, has been problematic for communicators. This article, the second in a Nutrition Today series examining evolving communication issues in the digital age, explores the implications of the reported declining trust in science communications. The authors cite a new definition of trust, suggested at a National Academies of Science workshop, and they report recent survey findings on public trust. After a detailed discussion of the implications of these findings, the authors offer some guidance to nutrition and health communicators on meeting evolving trust challenges.